The Radical Disciple: wholehearted Christian living - Stott, John R. W. (Nottingham, England: IVP, 2010)
Contents: Nonconformity -- Christlikeness -- Maturity -- Creation-care -- Simplicity -- Balance -- Dependence -- Death -- Conclusion -- Postscript : Farewell!
Keywords: Christian life -- Anglican authors -- 21st Century; Spirtiual life -- Biblical teaching